1994
DOI: 10.1021/ma00091a028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Highly Fluorinated Polyimides

Abstract: A series of polyimides was synthesized to facilitate the study of several structure/property relationships, including relative permittivity, moisture absorption, free volume, and viscoelastic transitions. This series was based on hexafluoroisopropylidene bis(phthalic anhydride) and various diamines, with the intention of having a number of fluorine/hydrogen and symmetric/asymmetric analog sets. Since several of the fluorinated diamines were exceptionally unreactive, a multistep polycondensation polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
197
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(206 citation statements)
references
References 6 publications
(6 reference statements)
7
197
1
Order By: Relevance
“…The dielectric constant of pure PI is 3.3 at 150°C, which is comparable to the values previously reported ͑2.9-3.4͒. 13 The decrease of dielectric constant with increasing PEO content is simply due to the more free volume ͑pores, Јϳ 1͒ generated with more PEO. It can also be found that the dielectric constant of the foamed film with 10 wt % PEO is below 2.6 in the temperature range from −150 to 150°C, which is satisfied to the required dielectric constant ͑ ഛ2.7͒ for next-generation interlayer low-k dielectric materials.…”
supporting
confidence: 87%
“…The dielectric constant of pure PI is 3.3 at 150°C, which is comparable to the values previously reported ͑2.9-3.4͒. 13 The decrease of dielectric constant with increasing PEO content is simply due to the more free volume ͑pores, Јϳ 1͒ generated with more PEO. It can also be found that the dielectric constant of the foamed film with 10 wt % PEO is below 2.6 in the temperature range from −150 to 150°C, which is satisfied to the required dielectric constant ͑ ഛ2.7͒ for next-generation interlayer low-k dielectric materials.…”
supporting
confidence: 87%
“…PIs are particularly attractive in the microelectronics industry due to their high thermal stability (Td), high glass transition temperature (Tg), low dielectric constant, high resistivity, high breakdown field, inertness to solvent, radiation resistance, easy processability, etc [2,3]. Recently, the emergence of novel wide bandgap semiconductor (SiC, GaN or Diamond) devices aiming to operate between 200 °C and 400 °C make PIs as one of the most potential organic materials for the surface secondary passivation [4].…”
Section: Introductionmentioning
confidence: 99%
“…In electronics packaging, low dielectric materials minimize crosstalk and maximize signal propagation speed in devices. Hence the development of polyimides with increasingly lower dielectric constants has been the focus of several recent investigations [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%